2015
DOI: 10.1111/spol.12166
|View full text |Cite
|
Sign up to set email alerts
|

Mark Time: India's March to Universal Health Care Coverage

Abstract: This article evaluates the efforts underway in India to achieve universal health care coverage and the conditions that fostered its contemporary evolution. It finds that India's health system is characterized by private provision and financing, horizontal and vertical fragmentation, and weak governance arrangements. The article argues that these defining characteristics, which have solidified over time, account for poor health outcomes and make the system impervious to reforms as they deny the government lever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A number of empirical reviews have identified governance as a key factor shaping performance of social programs (Romzek and Johnston, 2005; Fernandez, 2009; Amirkhanyan et al ., 2011; Bali and Ramesh, 2015). Studies on health financing have focused extensively on the links between program design and performance, especially the effects of specific design elements such as resource collection, risk pooling and purchasing functions on performance measures such as financial protection, service utilization and financial sustainability (Lu and William, 2003; Llyod-Sherlock, 2006; Bansak and Raphel, 2007; Ekman et al ., 2008; Kwon, 2009; Witter and Garshong, 2009; Liu et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A number of empirical reviews have identified governance as a key factor shaping performance of social programs (Romzek and Johnston, 2005; Fernandez, 2009; Amirkhanyan et al ., 2011; Bali and Ramesh, 2015). Studies on health financing have focused extensively on the links between program design and performance, especially the effects of specific design elements such as resource collection, risk pooling and purchasing functions on performance measures such as financial protection, service utilization and financial sustainability (Lu and William, 2003; Llyod-Sherlock, 2006; Bansak and Raphel, 2007; Ekman et al ., 2008; Kwon, 2009; Witter and Garshong, 2009; Liu et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Canada, Cuba, U.K, Hong Kong) where they have been bulwarks of efficiency. The challenge in India stems from the operational and political dimensions: hospitals are administered by State governments, many of which suffer from weak fiscal and administrative capacities (Bali & Ramesh, 2015b). This is aggravated by, until recently, central government's own very limited leverage to intervene in service delivery or regulate standards of care due to its peripheral role in financing and provision of health care in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Health agencies in both state and central governments are staffed by non-specialists and career bureaucrats that are rotated across different agencies every few years which denies them opportunity to develop domain expertise. Hospital superintendents have limited autonomy and discretion in important administrative and personnel decisions (Bali & Ramesh, 2015b). At a political level, successive governments have been unable to divert more resources to these cash strapped hospitals (La Forgia & Nagpal, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving universal health coverage at a fiscally sustainable cost has been a key goal of governments in the developing world in recent decades (Bonilla-Chacin and Aguilera 2013;Hanvoravongchai 2013;Somanathan et al 2013;Marten et al 2014;Harimurti et al 2013;Bali and Ramesh 2015a). Despite their efforts in the form of increased expenditures and new programmes, a large share of total healthcare expenditure in developing countries continues to be financed by out-of-pocket payments (OOPs), for example, about 50 per cent of total health expenditure in China, India, Indonesia, Philippines and Vietnam (WHO 2016).…”
Section: Introductionmentioning
confidence: 99%